European cowpea landraces for a more sustainable agriculture system and novel foods. (29th May 2017) - Carvalho, Márcia; Bebeli, Penelope J; Pereira, Graça; Castro, Isaura; Egea‐Gilabert, Catalina; Matos, Manuela; Lazaridi, Efstathia; Duarte, Isabel; Lino‐Neto, Teresa; Ntatsi, Georgia; Rodrigues, Miguel; Savvas, Dimitrios; et al.
Abstract: BACKGROUND: Genetic diversity is fundamental to breeding programs and consequently has an important role in obtaining new varieties. To properly use the genetic diversity present in germplasm collections, a good knowledge of the agro‐morphological traits of each accession is needed. The aim of this study was to explore the production capacity of 24 cowpea landraces from southern Europe, through phenotypic characterization and evaluation in three different locations in Greece and Portugal. RESULTS: Most qualitative parameters tested showed a high stability among the three locations. A wide difference was observed among the three locations with respect to number of days to flowering, ranging from 55 to 99 days. Quantitative traits showed a higher genotype × environment than genetic variance component. In general, an inverse relationship between σ 2 ge / σ 2 g ratio (where σ 2 ge is genotype × genotype interaction and σ 2 g is genotype impact) and heritability value was observed. Principal component analysis was able to group accessions based on their origin. The first two principal components explained 97.52% of variation, being the number of seeds per plant, plant height and seed protein content, the traits which contributed most to variability. CONCLUSION: The results show that sufficient variation exists in different traits within landraces in the studied cowpea germplasm to pursue a breeding program. However, the quantitative traits showed a higher genotype × environment component. © 2017 Society of Chemical Industry